Mobilitätshemmnisse heterogener Arbeitskräfte in Deutschland - Arntz, Melanie (Journal for labour market research, 2011)
Internal migration rates in Germany are relatively low in international comparison. Identifying obstacles to interregional mobility is thus of major policy concern because the geographic mobility of labour may contribute to higher overall economic growth as well as a reduction of interregional employment disparities. This article presents a number of findings from a research project that aims at identifying institutional factors that reduce geographic mobility among unemployed jobseekers in Germany and that, at the same time, may also contribute to explaining the large gap in internal migration rates between qualified and unqualified workers. The findings indicate that a generous unemployment benefit system contributes to the observed phenomena. Workfare programs that reduce the partially high wage replacement rates among low-qualified unemployed might thus result in higher levels of internal migration in Germany.